Introduction to Sociology - Giddens, Anthony; Duneier, Mitchell; Appelbaum, Richard P.; Carr, Deborah (W. W. Norton, 2024)
"The most trusted textbook in sociology. With more than a million copies sold and counting, Introduction to Sociology is valued for its reliable and authoritative coverage of sociological concepts, theory, and research. This comprehensive survey of the field gives students everything they need to internalize core concepts and develop their sociological imaginations. Our stellar author team helps students understand key sociological insights and apply them to the big social issues of our time. New online learning resources support understanding and deep, engaged reading"--